Persistent infection of chimpanzees with human immunodeficiency virus: serological responses and properties of reisolated viruses. - Nara, P L (1987)
Persistent infection by human immunodeficiency virus (HIV-1) in the chimpanzee may be valuable for immunopathologic and potential vaccine evaluation. Two HIV strains, the tissue culture-derived human T-cell lymphotropic virus type IIIB (HTLV-IIIB) and in vivo serially passaged lymphadenopathy-associated virus type 1 (LAV-1), were injected intravenously into chimpanzees. Two animals received HTLV-IIIB as either virus-infected H9 cells or cell-free virus. A third animal received chimpanzee-passaged LAV-1. Evaluation of their sera for virus-specific serologic changes, including neutralizations, was done during a 2-year period. During this period all animals had persistently high titers of antibodies to viral core and envelope antigens. All three animals developed a progressively increasing type-specific neutralizing LAV-1 versus HTLV-IIIB antibody titer during the 2-year observation period which broadened in specificity to include HTLV-HIRF, HTLV-IIIMN, and HTLV-IIICC after 6 to 12 months. The antibody titers against both viruses were still increasing by 2 years after experimental virus inoculation. Sera from all animals were capable of neutralizing both homologously and heterologously reisolated virus from chimpanzees. A slightly more rapid type-specific neutralizing response was noted for the animal receiving HTLV-IIIB-infected cells compared with that for cell-free HTLV-IIIB. Sera from all persistently infected chimpanzees were capable of mediating group-specific antibody-mediated complement-dependent cytolysis of HIV-infected cells derived from all isolates tested. Viruses reisolated from all three animals at 20 months after inoculation revealed very similar peptide maps of their respective envelope gp120s, as determined by two-dimensional chymotrypsin oligopeptide analysis. One peptide, however, from the original HTLV-IIIB-inoculated virus was deleted in viruses from all three animals, and in addition, we noted the appearance of a new or modified peptide which was common to LAV-1 as well as to HTLV-IIIB reisolated from infected chimpanzees. It thus appears that a group-specific neutralizing antibody response as well as a group-specific cytotoxic response can develop in chimpanzees after an inoculation of a single HIV variant. This finding suggests that a common, less immunodominant determinant(s) is present on a single HIV strain which could induce group-specific antibodies during viral infection and replication. The identification of this group-specific epitope and the induction of analogous immunity may be relevant to vaccine development against human acquired immunodeficiency syndrome.